ANALYSIS OF A SOLAR PHOTOVOLTAIC SYSTEM TO SUPPORT THE ENERGY REQUIREMENTS OF LIQUID CRYSTAL DISPLAY (LCD) PROJECTORS IN THE FACULTY OF ENGINEERING BUILDING 2, UNIVERSITAS TIDAR - Arbye S; Feri Adriyanto (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
This study presents the analysis and design of a small-scale off-grid solar photovoltaic (PV) system to supply the electrical energy requirements of Liquid Crystal Display (LCD) projectors used in nine classrooms at Faculty of Engineering Building 2, Universitas Tidar. LCD projectors operate for approximately 10–11 hours per day, resulting in a total daily energy demand of 29.7 kWh. The objective of this research is to (1) analyze the daily load profile of projector usage, (2) determine the appropriate capacity of PV modules, batteries, and inverter, and (3) evaluate the techno-economic feasibility of the proposed system. Data collection was carried out through field observation, device power measurement, rooftop area assessment, and retrieval of solar irradiation data. The system design combines manual engineering calculations with optimization using HOMER Pro software. Results indicate that a PV capacity between 9–10.5 kWp is sufficient to fulfill daily load demand. HOMER simulation recommends an optimal configuration consisting of a 9 kWp PV array, a 3.2 kW inverter, and 17 battery units, yielding a Net Present Cost (NPC) of USD 23,874.79 and a Levelized Cost of Energy (LCOE) of USD 0.296/kWh. The system achieves 100% renewable fraction with minimal shortage. Overall, the designed PV system is technically and economically feasible and can serve as a practical applied-learning resource for engineering students studying renewable energy systems.